THE EFFECT OF COMPENSATION, COMPETENCE, AND LEADERSHIP ON MINISTRY OF INDUSTRION'S PUBLIC EMPLOYEES PERFORMANCE - Jailani; Lenny C. Nawangsari (Dinasti Publisher, 2020)
The purpose of this research is to investigate the effect of compensation, competence and leadership on employee performance. This research was conducted at the Ministry of Industry, the responses used were 81 employees in the Ministry of Industry. The data processed by using Statistical Package for the Social Sciences (SPSS) Version 24. The resultsof this research showing that compensation has no effect and no significant effect on performance, on the other hand competence has significant effect on performance and also leadership has significant effect on performance.